2018
DOI: 10.1590/0034-7167-2018-0308
|View full text |Cite
|
Sign up to set email alerts
|

Nursing professionals' knowledge regarding the management of waste produced in primary health care

Abstract: Objective: To evaluate the knowledge of Nursing professionals regarding waste management in primary healthcare services. Method: Descriptive study with a mixed approach, developed with 42 nursing professionals who worked in basic health units of a capital in the Brazilian Northeast Region. Quantitative variables were analyzed by the SPSS 20.0 program. Reports were processed by the IRaMuTeQ software, analyzed according to the descending hierarchical classification, and grounded on the Collective Subject Discou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
7
0
4
Order By: Relevance
“…The only variable of the present study that is associated with professional knowledge on the subject was the length of experience in PHC so that, statistically, the longer the experience in PHC the greater the number of correct answers in the questionnaires. In this regard, the analysis of the sociodemographic profile of the respondents showed professionals who have worked in these services for a long time, with more than 20 years of initial education, as well as one or more Graduate studies, as corroborated by other studies (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 55%
“…The only variable of the present study that is associated with professional knowledge on the subject was the length of experience in PHC so that, statistically, the longer the experience in PHC the greater the number of correct answers in the questionnaires. In this regard, the analysis of the sociodemographic profile of the respondents showed professionals who have worked in these services for a long time, with more than 20 years of initial education, as well as one or more Graduate studies, as corroborated by other studies (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 55%
“…Os demais artigos relataram a gestão do conhecimento dos profissionais de saúde, treinamentos, novas formas de tratamento de efluentes e gestão de resíduos hospitalar. Treinamento e aperfeiçoamento por: (DEHGHANI et al, 2019;FERRANTE et al, 2018;GUNAWARDANA, 2018;HASAN;RAHMAN, 2018;NITIKA et al, 2017;PURI et al, 2019;DERESS et al, 2018;FLORELIA et al, 2015;RATHORE;JACKSON, 2017;MATOS et al, 2018;DEMETRIAN et al, 2019;ZEESHAN et al, 2018;KUMAR et al, 2015;JOSHI et al, 2015;ARA et al, 2019).…”
Section: Resultados E Discussõesunclassified
“…Due to the lack of this specific environment, as well as the lack of knowledge of the legislation, ANVISA norms and management technique, professionals are taken to store the waste in environments where other types of activities are performed and, often, the waste is disposed of in the unit outdoor patio environment. 8,12,13,14,15 Once collected at its internal storage site, waste is collected for its treatment and final destination. In most health care units, this process is performed by outsourced collection and treatment companies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inadequate final destination of waste, as well as the failure or lack of treatment, can lead to contamination of the environment from the ground, groundwater, to air and impact on the health of animals, individuals and communities. 11,15 Given the above, it appears that the management of solid waste in the PHC of the municipality in question is not in accordance with the provisions of Brazilian law. It was found that they do not follow a HCWMP so that their management is done correctly.…”
Section: Discussionmentioning
confidence: 99%